TiNi-based material with shape-memory effect for surgical treatment of diseases of small intestine in newborn and young children - Anikeev, Sergey G.; Kaftaranova, Maria I.; Khodorenko, Valentina N.; Ivanov, Stanislav D.; Artyukhova, Nadezhda V.; Shabalina, Anastasiia V.; Kulinich, Sergei A.; Slizovsky, Grigory V.; Mokshin, Anatolii V.; Gunther, Victor E. (Journal of functional biomaterials)
Alloys based on TiNi are widely used in various fields of technology and medicine. In the present work, we report on the preparation of TiNi-alloy-based wire with the shape-memory effect, which was used for compression clips for surgery. The composition and structure of the wire and its martensitic and physical–chemical properties were studied using SEM, TEM, optic microscopy, profilometry, mechanical tests, etc. The TiNi alloy was found to consist of B2 and B19’ and secondary-phase particles of Ti2Ni, TiNi3 and Ti3Ni4. Its matrix was slightly enriched in Ni (50.3 at.% of Ni). A homogeneous grain structure was revealed (an average grain size of 19 ± 0.3 µm) with equal quantities of grain boundaries of special and general types. The surface oxide layer provides improved biocompatibility and promotes the adhesion of protein molecules. Overall, the obtained TiNi wire was concluded to exhibit martensitic, physical and mechanical properties suitable for its use as an implant material. The wire was then used for manufacturing compression clips with the shape-memory effect and applied in surgery. The medical experiment that involved 46 children demonstrated that the use of such clips in children with double-barreled enterostomies permitted improvement in the results of surgical treatment.